Innovations in low-income country food systems - Michelson, Hope C. (International Food Policy Research Institute, 2024)
The food sector is a critical area of employment and economic activity in most low-income countries, especially for the rural poor, providing incomes and sustenance, employment and growth. In many low and middle-income countries, two configurations, formal and informal, overlap in economically significant grey areas. This overlap between the formal and informal is particularly common and therefore relevant to research and policy in the food sector of low-income countries. This paper is concerned with identifying innovations in the informal sector of food systems in low-income countries, in particular innovations that improve participation and circumstances for those at the bottom: farmers, small traders. This focus requires some distinction between formal and informal; this distinction will abstract away from a lot of the overlap and the dynamism of the sector. We organize the definition of formal and informal primarily around the degree of compliance with official regulatory frameworks and financial systems, acknowledging that this definition has some limitations. For example, the nature of activities and actors in the informal sector—such as smaller firm size or transaction size—can in some cases mean that their operations are not subject to the regulations that apply to larger firms. Formality, in such economies and under such a definition, is then tightly correlated not just with regulatory compliance but also the economic scale of the operations (which may be endogenously determined as a means of avoiding regulation). While this framework helps to clarify the boundaries of what is considered formal or informal, is important to recognize that these boundaries can be fluid, and in many contexts, the distinction may not fully capture the nuanced realities of economic activity.